Music performance anxiety in instrumental duos: six interviews - Fiammetta Facchini Giuseppina Facchini; Nancy Lee Harper (Orfeu, 2018)
Abstract Six semi-structured interviews with members of long-terms chamber music duo (violin and piano; cello and piano; piano 4 hands) were realised with the objective to analyse what happens in terms of Musical Performance Anxiety (MPA) in long-term Duo ensembles. The analysis showed that MPA is some common to all musicians but, at the same time, for these interviewed musicians, the “Duo” is a refuge, a safe place where they feel protected that is impossible to compare to “solo” performance. Regarding the causes of MPA in duo performance, it seems that factors of the family and the context in which the musician has grown up have a strong impact on the degree of experiencing more, or less, anxiety about public performance. As well, personal characteristics have a large impact on the development and degree of MPA.  It seems too that there is a kind of reluctance to speak about MPA between musicians and it also emerged that there is a lack of an education system that promotes knowledge and the development of coping strategies to deal with MPA. With respect to solving the matter of MPA, a different attitude is noted across the generations, given the difference in ages of the duos but, in general, we find here many agreements among all respondents about the fact that an appropriate study, done in a rational and conscious way along with a positive psycho-somatic attitude and a healthy lifestyle and the application of breathing techniques and concentration, are actually effective means to counter the problems of MPA. Regarding the difference between a consolidated and an occasional Duo, all stated that within the consolidated Duo there is another perception, another poetry.